A wild cowboy - Smith, Danna; Freeman-Hines, Laura (New York : Jump at the Sun/Hyperion Books for Children, 2004)
A young cowboy and his younger brother spend an action-packed day at their Grandmother's place.
Keywords: Cowboys -- Fiction; African Americans -- Fiction; Grandmothers -- Fiction; Stories in rhyme